Deep dive into the immune response against murine mesothelioma permits design of novel anti-mesothelioma therapeutics - Stern, Esther; Caruso, Stefano; Meiller, Clément; Mishalian, Inbal; Hirsch, Theo Z.; Bayard, Quentin; Tadmor, Carmit T.; Wald, Hanna; Jean, Didier; Wald, Ori (Frontiers in Immunology, 2023)
Given the need to improve the efficacy of standard-of-care immunotherapy (anti-CTLA-4 + anti-PD-1) in human malignant pleural mesothelioma (hMPM), we thoroughly characterized the immunobiology of the AB12 murine mesothelioma (MM) model, aiming to increase its accuracy in predicting the response of hMPM to immunotherapy and in designing novel anti-hMPM treatments. Specifically, we used immunologic, transcriptomic and survival analyses, to synchronize the MM tumor growth phases and immune evolution with the histo-molecular and immunological characteristics of hMPM while also determining the anti-MM efficacy of standard-of-care anti-hMPM immunotherapy as a benchmark that novel therapeutics should meet. We report that early-, intermediate- and advanced- AB12 tumors are characterized by a bell-shaped anti-tumor response that peaks in intermediate tumors and decays in advanced tumors. We further show that intermediate- and advanced- tumors match with immune active (“hot”) and immune inactive (“cold”) hMPM respectively, and that they respond to immunotherapy in a manner that corresponds well with its performance in real-life settings. Finally, we show that in advanced tumors, addition of cisplatin to anti CTLA-4 + anti PD-1 can extend mice survival and invigorate the decaying anti-tumor response. Therefore, we highlight this triple combination as a worthy candidate to improve clinical outcomes in hMPM.